2014
DOI: 10.1155/2014/826970
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Efficacy of 50% Autologous Serum Eye Drops in Different Ocular Surface Pathologies

Abstract: Purpose. This study evaluated the efficacy of 50% autologous serum eye drops in ocular surface diseases not improved by conventional therapy. Methods. We analyzed two groups: (1) acute eye pathologies (e.g., chemical burns) and (2) chronic eye pathologies (e.g., recurrent corneal erosion, neurotropic keratitis, and keratoconjunctivitis sicca). The patients were treated for surface instability after conventional therapy. The patients received therapy 5 times a day until stabilization of the framework; they then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 62 publications
0
40
0
3
Order By: Relevance
“…Concentrations of 50-100% autologous serums are recommended for moderate to severe dry eye. [36][37][38][39] ASED are safe to use daily long term. Bacterial contamination and preservation of the components in ASED is not a concern provided the ASED are cold stored properly (unopened vials for six months in the freezer or open vials for seven days in a refrigerator).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concentrations of 50-100% autologous serums are recommended for moderate to severe dry eye. [36][37][38][39] ASED are safe to use daily long term. Bacterial contamination and preservation of the components in ASED is not a concern provided the ASED are cold stored properly (unopened vials for six months in the freezer or open vials for seven days in a refrigerator).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial contamination and preservation of the components in ASED is not a concern provided the ASED are cold stored properly (unopened vials for six months in the freezer or open vials for seven days in a refrigerator). 37,39 Typical dosing is between six times daily to every two hours for moderate to severe dry eye. 35,37 ASED are only contraindicated in patients with blood-borne pathogenic diseases such as human immunodeficiency virus or hepatitis B.…”
Section: Discussionmentioning
confidence: 99%
“…8 In 1 study, a patient experienced a recurrence of the epithelial defect when the serum-based eye drops were discontinued. 19 In another study, 1 of the bottles of serum eye drops was found to have microbial growth that matched the bacterium (Serratia marcescens) cultured from the patient's corneal lesion. 8…”
Section: Nonhealing Corneal Epithelial Defectmentioning
confidence: 96%
“…8,17e19 All showed substantial improvement in the epithelial defects, and 3 showed a reduction of more than 90% in the size of the defects. 8,18,19 A study comparing 50% versus 100% serum concentration found faster closure of the epithelial defects in patients using the 100% concentration eye drops. 8 In 1 study, a patient experienced a recurrence of the epithelial defect when the serum-based eye drops were discontinued.…”
Section: Nonhealing Corneal Epithelial Defectmentioning
confidence: 99%
“…In a previous study, we recorded a significant improvement in the signs and symptoms after therapy with eye drops in patients with different ocular surface disorders (25). The main objective of this study was to investigate the mechanisms by which AS eye drops are able to ameliorate alterations in the corneal epithelium and sub-basal nervous plexus in patients with SSDE.…”
mentioning
confidence: 93%